E-cadherin loss of function in the murine intestine - Matheson, JAH (2012)
E-cadherin (Cdh1), is a major component of epithelial adherens junctions, binds the Wnt pathway effector β-catenin and is lost at the invasive edge of colon cancers. Crypt stem cells give rise to 4 cell lineages that, with the exception of Paneth cells, travel along the crypt-villus axis over 3 days and are shed by anoikis. Gain of function of the Wnt pathway by a mutation in Adenomatous Polyposis Coli (Apc) disrupts enterocyte turnover to result in adenoma formation. Homozygote null Cdh1 is embryonic lethal, and heterozygote Cdh1 can promote Apc1638N induced adenoma formation, but we lack models that assess additional functions of Cdh1 in the adenoma to carcinoma transition. The aim of this thesis was to evaluate the effect of Cdh1 loss of function in the murine intestine, including in the setting of Wnt pathway activation. To do this, germline and intestinal specific conditional Cdh1 loss of function models were generated. Conditional homozygous deletion of Cdh1 resulted in embryonic lethality using Villin-Cre. In adults, homozygous Cdh1 loss using the tamoxifen inducible Villin-CreERT2 led to intestinal inflammation, bacteraemia and disrupted crypt-villus architecture. Combined conditional homozygous deletion of Cdh1 and Apc resulted in Wnt pathway upregulation assessed by β-catenin immunolabelling. Strain dependent effects of Cdh1 heterozygosity were apparent on the Apc heterozygote background: ApcMin/+ Cdh1+/- (C57BL/6J) had no effect on survival or adenoma phenotype compared to littermate ApcMin/+; Cdh1+/fl increased adenoma burden in Apc+/fl Vil-Cre animals (B6D2/C57BL/6J). Low frequency recombination of Apcfl/fl using Lgr5-EGFP-IRES-CreERT2 bypasses the loss of heterozygosity event relied on in heterozygous Apc tumour models achieving a large adenoma burden within 4 weeks. Cdh1 loss did not alter survival or adenoma phenotype in this model, including the development of large caecal tumours. Immunolabelling of tumours from Apcfl/fl Cdh1fl/fl animals showed persistent E-cadherin protein expression, suggesting incomplete recombination or that double homozygote enterocytes failed to survive. In vitro adenoma culture was used to test whether E-cadherin loss was incompatible with enterocyte survival in the setting of Wnt activation. Apcfl/fl Cdh1+/+ and Apcfl/fl Cdh1fl/fl adenoma were cultured in matrigel and treated with an adenovirus expressing Cre recombinase under a CMV promoter (Ad-Cre). Ad-Cre had no effect on Apcfl/fl Cdh1+/+ adenoma growth. Ad-Cre treated Apcfl/fl Cdh1fl/fl adenoma organoids showed cells where E‑cadherin loss resulted in Wnt pathway upregulation as assessed by nuclear β-catenin and Axin2 expression, and epithelial mesenchymal transition shown by upregulation of fibronectin, twist and vimentin. This work supports a role for E-cadherin in modulation of the Wnt pathway. Further investigation is required to define the cell adhesion versus Wnt regulatory functions of E-cadherin.